2006
DOI: 10.1161/01.atv.0000228819.13039.b8
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Diet During Pregnancy and Carotid Intima–Media Thickness in Children

Abstract: Objective-Autopsy studies show that intimal lipid accumulations in arteries are often present at birth, suggesting that the prenatal environment plays a role in the pathogenesis of atherosclerosis. In animal models, a restricted or unbalanced maternal diet during gestation can influence susceptibility to atherosclerosis, but the relation in humans between maternal diet during pregnancy and atherogenesis is unknown. Methods and Results-We measured carotid intima-media thickness (IMT) in 216 nine-year-old childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 34 publications
0
74
1
1
Order By: Relevance
“…34 In the present study, BP (both systolic and diastolic) was a major determinant of cIMT; this is consistent with previous reports of the determinants of cIMT in adults [35][36][37] and in children. 38,39 However, in the present study, low-density lipoprotein cholesterol was unrelated to childhood cIMT, whereas skinfold thickness and triglyceride levels were inversely related. Although earlier studies have suggested that both adult and childhood low-density lipoprotein cholesterol levels are associated with adult cIMT, 40 -42 previous evidence for an association between low-density lipoprotein cholesterol and cIMT in childhood is primarily based on small studies comparing children with and without familial hypercholesterolemia, in whom low-density lipoprotein cholesterol differences are marked.…”
Section: Relation To Earlier Studiescontrasting
confidence: 73%
See 1 more Smart Citation
“…34 In the present study, BP (both systolic and diastolic) was a major determinant of cIMT; this is consistent with previous reports of the determinants of cIMT in adults [35][36][37] and in children. 38,39 However, in the present study, low-density lipoprotein cholesterol was unrelated to childhood cIMT, whereas skinfold thickness and triglyceride levels were inversely related. Although earlier studies have suggested that both adult and childhood low-density lipoprotein cholesterol levels are associated with adult cIMT, 40 -42 previous evidence for an association between low-density lipoprotein cholesterol and cIMT in childhood is primarily based on small studies comparing children with and without familial hypercholesterolemia, in whom low-density lipoprotein cholesterol differences are marked.…”
Section: Relation To Earlier Studiescontrasting
confidence: 73%
“…56,57 However, in the UK population, South Asians rather than black AfricanCaribbeans have the lowest mean birth weight and the highest prevalence of low birth weight. 58 Maternal factors, particularly maternal cigarette smoking and low maternal energy intake, are associated with increased offspring cIMT 38,59 and need further exploration. Genetic factors could also be important, although their role remains uncertain.…”
Section: Explanations For Cimt Patternsmentioning
confidence: 99%
“…Similarly, there is evidence that variation in maternal nutrition within the usual range of intakes of Western women can affect fetal physiology, size at birth and subsequent endothelial function in childhood. [41][42][43][44] There is a very large body of experimental evidence (for review, see McMillen and Robinson 45 ) relating altered fetal development to later obesity and metabolic compromise. These studies, usually performed in rodents or sheep, typically challenge fetal development by reducing overall maternal nutrition, by specifically reducing maternal protein intake or by administering glucocorticoids to the mother.…”
Section: The 'Mismatch' or 'Thrifty' Pathwaymentioning
confidence: 99%
“…Specific aspects of the developmental environment, such as the mother’s diet or her body composition, stress levels, and her level of physical activity, have also been shown to be risk factors for later disease. For example, Gale et al [14] showed that a mother’s energy intake in late pregnancy was related to carotid intima-media thickness (an early marker of vascular disease) in 9-year-old children – an effect amplified by the child’s weight at age 9. As these studies were conducted in an unselected population in a European city, they clearly demonstrate how risk is graded across the spectrum of normal human development.…”
Section: Developmental Mismatchmentioning
confidence: 99%